2023
DOI: 10.1186/s42836-023-00216-0
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, prospective cohort study: immediate postoperative gains in active range of motion following robotic-assisted total knee replacement compared to a propensity-matched control using manual instrumentation

Camdon Fary,
Jason Cholewa,
Anna N. Ren
et al.

Abstract: Background Range of motion (ROM) following total knee replacement (TKR) has been associated with patient satisfaction and knee function, and is also an early indicator of a successful procedure. Robotic-assisted TKR (raTKR) is considered to reproduce more precise resections, and, as a result, may be associated with improved early patient satisfaction compared to manual TKR (mTKR). The purpose of this study was to evaluate the early postoperative active ROM (aROM) between raTKR and mTKR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Compared with C-TKR, R-TKR resulted in less loss of ROM immediately after surgery and faster recovery of ROM within three months after operation. Cadmon et al [ 44 ] showed that active ROM was significantly greater than 5.1° and 2.9° at one- and three-month follow-up, respectively, in patients operated with R-TKA compared to C-TKA. With respect to preoperative ROM, the improvement was higher in patients with R-TKA compared to C-TKA: 6.9° at 1-month follow-up and 4.9° at 3-month follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with C-TKR, R-TKR resulted in less loss of ROM immediately after surgery and faster recovery of ROM within three months after operation. Cadmon et al [ 44 ] showed that active ROM was significantly greater than 5.1° and 2.9° at one- and three-month follow-up, respectively, in patients operated with R-TKA compared to C-TKA. With respect to preoperative ROM, the improvement was higher in patients with R-TKA compared to C-TKA: 6.9° at 1-month follow-up and 4.9° at 3-month follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…At long-term follow-up, knee ROM is significantly improved in both robotic and conventional TKA compared to preoperative status, but no statistically significant differences have been reported [ 44 , 45 ]. Lee et al [ 46 ] reported on 855 knees (194 robotic group, 391 navigational group, and 270 conventional group) comparing clinical and radiological outcomes during a minimum follow-up period of 10 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation